'Theodor Neubauer bei Clara Zetkin in Birkenwerder'. From: Bro 1746/10. Original photo at: IML-Berlin (1931)
'Theodor Neubauer bei Clara Zetkin in Birkenwerder'. From: Bro 1746/10. Original photo at: IML-Berlin.